Compliance of a Government Act on Cigarettes and Other Tobacco Products around Educational Institutions of Noida - Shibli Sayeed; Satyanarayana Labani; Smita Asthana (Open Journal of Bioinformatics and Biostatistics - Peertechz Publications, 2017)
Objectives: The aim of study was to evaluate the Compliance to the Government Act on Cigarettes and Other Tobacco Products (COTPA Act 2003) Section 6 that protects the exposure of under 18 children to tobacco products and to identify areas of violations, near Educational Institutions (EIs) in Noida. Study Design: Cross-sectional field study. Methods: Observational cross sectional survey was done on compliance of COTPA Act 2003 section 6 by tobacco Vendors situated within 100 yards of EIs of Noida using a questionnaire. The questionnaire consisted of 21 questions which included the criteria related to tobacco-free provisions of Section 6 of COTPA Act 2003. Results: The display of sign boards of "NO Tobacco" compliance was 7% in private schools and zero percent in government schools. In thirty fi ve percent of schools at least one vendor was situated at within 100 yards of school. The violation was seen at points of sale (POS) of tobacco products as well as around the EIs such as sale of tobacco products by minors (6.7%) and to the minors (37.1%). Conclusions: Implementation of tobacco control policy COTPA Act 2003 section 6 needs further emphasis. The schools and the local district health authorities should be made aware of the extent of non-compliance of COTPA Act 2003 and be made stakeholders to reduce tobacco use by Minors.